Disgrafía y su repercusión en el lenguaje escrito de los estudiantes de la unidad educativa “León de Febres Cordero de la parroquia San Juan, cantón Puebloviejo provincia los Ríos - Rivas García, Santa Emperatriz (2017)
This research work was carried out with the purpose of showing as the valuation of Dysgraphia in the teaching process improves the performance of the language written in the students, to which were a large number of queries in physical and electronic sources different concepts, meanings and theories that allowed to understand and explain in better shape the relationship between the variables in this work of degree corresponding to the linguistic area , as it is considered that bad writing in the years of basic education has been a growing problem that affected the performance written in the students of the educational unit "León de Febres Cordero" from Puebloviejo canton. It is a non-experimental methodical thesis that followed three levels of (exploratory and explanatory and descriptive) research with a sample of 161 students and 23 teachers that were surveyed, an along with the calculation of the formula chi square could confirm the validity of the assumptions made, this was after having chosen a question, the same one that was chosen to have a high degree of relevance and importance between the two variables. Once the results were analyzed the author considered the along with the calculation of the formula chi square could confirm the validity of the assumptions made, this was after having chosen a question, the same one that was chosen to have a high degree of relevance and importance between the two variables. Once the results were analyzed the author considered the conclusions and specific recommendations to help eradicate the problem which was the subject of this investigation.